Restrictions on Congregational Prayers and Negotiations on Religious Freedom during Pandemic in Indonesia - Alamsyah M. Dja'far (Indonesian Journal of Political Studies, 2021)
This article discusses the policy of restricting religious rights or beliefs during the pandemic time in Indonesia. Most studies presume that restriction policy is in line with the principles and rights of religious freedom. These studies have not much directed towards answering how the restriction on the worship right, such as congregational prayers, able to accommodate and negotiate various rejections and neglects by some Islamic communities. This paper comes with the idea that policies to restrict congregational prayers should not be uniform but provide several alternative approaches. This approach needs support from central and local authorities negotiating abilities. The main research data came from the policy documents of the central government and provincial government. Secondary data came from media coverage and relevant literature. This study found that restrictions in the early days of the pandemic applied uniformly in the form of the absence of congregational prayers during the lockdown period. The policy does not provide alternatives such as still allowing it by establishing health protocols.